Influence of Different Prebiotics on Viability of Lactobacillus casei, Lactobacillus plantarum and Lactobacillus rhamnosus Encapsulated in Alginate Microcapsules - Luca, Liliana (Foods, 2021)
As the production and maintenance of a sufficient number of microencapsulated probiotics is still a test for the food industry, the present study addressed the testing of three prebiotics: chicory inulin, soluble potato starch, oligofructose and a control carbon source, namely glucose, as a component part of the encapsulation matrix. Using the extrusion encapsulation technique, it was possible to obtain microcapsules whose matrix composition and dimensions correspond to the requirements of the food industry. The microcapsules obtained showed significantly different physicochemical properties, with different survival rates during processing, storage and in simulated gastrointestinal conditions. The encapsulation efficiency was very high in relation to the dimensions of the microcapsules and the technique used (between 87.00–88.19%). The microcapsules obtained offered a very good viability (between 8.30 ± 0.00–9.00 ± 0, 02 log10 cfu/g) during the 30 days of storage at 2–8 degrees and also in the simulated gastrointestinal conditions (between 7.98–8.22 log10 cfu/g). After 30 days, the lowest viability was registered in the microcapsules with glucose 6.78 ± 0.15 log10 cfu/g. It was found that after 4 h of action of gastrointestinal juices on the microcapsules stored for 30 days, cell viability falls within the limits recommended by the Food and Agriculture Organization of the United Nations (FAO) (10(6)–10(7) CFU/mL or g of food. This study demonstrated that using prebiotic encapsulation matrix increases cell viability and protection and that the extrusion encapsulation method can be used in the production of probiotic microcapsules for the food industry.